Wide-supply integration CMOS DC-DC converter for energy harvesting applications - Nur Allisa Sabrina, Amin (2023)

(untitled)
This study describes the design, analysis, and simulation of a Wide-Supply Integrated CMOS DC-DC Converter in the goal of creating energy-efficient technology for energy harvesting applications. Cross couple charge pump is utilized in this design to to meet the special requirements of energy harvesting systems by effectively capturing and converting captured energy into suitable voltage levels. Furthermore, this paper proposed DC-DC converter that improve the existence charge pump like Dickson Charge Pump (DCP) by adding Pulse Frequency Modulation (PFM) to enhance the performance and generate a high voltage output with a variety of supply voltages. By accomplishing its goals, this study advances energy-efficient technologies and has great potential for integrated circuit systems and a variety of energy harvesting projects.